Parasitic infestation of intradermal chiggers Hannemania achalai (Acari: Leeuwenhoekiidae) on the cryptic species Pleurodema kriegi and P. cordobae (Anura: Leptodactylidae: Leiuperinae) from Sierra Grande, Córdoba, Argentina - Biolé, Fernanda Gabriela (2015)
Chiggers of the genus Hannemania occur in the Americas and are intradermal parasites of amphibians. In the present study, we examine the infestation of Hannemania achalai on the sister anuran species Pleurodema kriegi and P. cordobae. A total of 248 individuals were examined to quantify prevalence, mean abundance and mean intensity of infestation. Infestation rates in P. kriegi juveniles were lower than in adults. The abundance and intensity of infestation did not differ between host sexes. In adults, chigger prevalence on P. kriegi (92%) was notably higher than on P. cordobae (42%), which is also reflected in mean intensity (40.3 and 14.4 chiggers per infested host, respectively) and abundance (36.9 and 6.0 chiggers per individual, respectively) between species. The vent region and hind limbs had the highest parasite load. This study for the first time reports the presence of this parasite in P. cordobae, and represents the first comparative study of population estimators and Hannemania preference between taxonomically related species of frogs.